Association Between Obesity Type and Common Vascular and Metabolic Diseases: A Cross-Sectional Study - Zhang, Peng; Sun, Xin; Jin, Hang; Zhang, Fu-Liang; Guo, Zhen-Ni; Yang, Yi (Frontiers in Endocrinology, 2020)
Background: The association between different types of obesity and some chronic diseases in Dehui, Jilin province, China, is still unclear. The aim of our study was to clarify the association between different types of obesity and chronic diseases. Methods: Residents aged 40 years or older were randomly selected using a multistage stratified cluster sampling method. Data were collected by means of face-to-face interview, physical examination and laboratory examination. Descriptive data analyses were performed, and multiple logistic regression analyses were used to explore the adjusted association between different types of obesity and common vascular and metabolic diseases. Results: The prevalence of general obesity alone, central obesity alone and compound obesity were 0.15%, 54.29% and 14.36%, respectively. The prevalence of coronary heart disease, stroke, hypertension, dyslipidemia and diabetes mellitus was highest in the compound obesity group, and lowest in the non-obesity group. Hypertension, dyslipidemia, and diabetes mellitus were associated with compound obesity and central obesity alone (compound obesity [OR=4.703, 95% CI: 3.714-5.956 for hypertension; OR=4.244, 95% CI: 3.357-5.365 for dyslipidemia; OR=4.575, 95% CI: 3.194-6.552 for diabetes mellitus]; central obesity alone [OR=2.210, 95% CI: 1.901-2.570 for hypertension; OR=2.598, 95% CI: 2.241-3.012 for dyslipidemia; OR=2.519, 95% CI: 1.834-3.459 for diabetes mellitus]). Coronary heart disease was associated with compound obesity (OR=1.761, 95% CI: 1.141-2.719) but not central obesity alone (OR=1.409, 95% CI: 0.986-2.013). Stroke was associated with neither compound obesity (OR=1.222, 95% CI: 0.815-1.833) nor associated with central obesity alone (OR=1.080, 95% CI: 0.786-1.485). Conclusions: Central obesity alone and compound obesity are associated with the risk of hypertension, hyperlipidemia and diabetes mellitus. Compound obesity but not central obesity alone is associated with the risk of coronary heart disease, but further research is needed to confirm it. There are no significant relationship between stroke and central obesity alone or compound obesity.